Genomic Variation and Arsenic Tolerance Emerged as Niche Specific Adaptations by Different Exiguobacterium Strains Isolated From the Extreme Salar de Huasco Environment in Chilean – Altiplano - Castro-Severyn, Juan; Pardo-Esté, Coral; Mendez, Katterinne N.; Morales, Naiyulin; Marquez, Sebastián L.; Molina, Franck; Remonsellez, Francisco; Castro-Nallar, Eduardo; Saavedra, Claudia P. (Frontiers in Microbiology, 2020)
Polyextremophilic bacteria can thrive in environments with multiple stressors such as the Salar de Huasco (SH) environment. Microbial communities in SH are exposed to high atmospheric pressure, high UV radiation, wide temperature ranges, salinity gradient and the presence of toxic compounds such as arsenic (As). In this work we focus on arsenic stress as one of the main adverse factors in SH and bacteria that belong to the Exiguobacterium genus due to their plasticity and ubiquity. Therefore, our aim was to shed light on the effect of niche conditions, particularly arsenic pressure, on the adaptation and divergence (at genotypic and phenotypic levels) of Exiguobacterium strains from five different SH sites. Also, to capture greater diversity in this genus, we use as outgroup five As(III) sensitive strains isolated from Easter Island (Chile) and The Great Salt Lake (USA). For this, samples were obtained from five different SH sites under an arsenic gradient (9 to 321 mg / kg: sediment) and isolated and sequenced the genomes of 14 Exiguobacterium strains, which had different arsenic tolerance levels. Then, we used comparative genomic analysis to assess the genomic divergence of these strains and their association with phenotypic differences such as arsenic tolerance levels and the ability to resist poly-stress. Phylogenetic analysis showed that SH strains share a common ancestor. Consequently, populations were separated and structured in different SH microenvironments, giving rise to multiple coexisting lineages. Hence, this genotypic variability is also evidenced by the “Clusters of Orthologous Groups” (COG) composition and the size of the accessory genome compartments. Interestingly, these observations correlate with physiological traits such as growth patterns, gene expression, and enzyme activity related to arsenic response and/or tolerance. Therefore, Exiguobacterium strains from SH are adapted to physiologically overcome the contrasting environmental conditions, like the arsenic present in their habitat.